Behaviour of captive ostriches (Struthio camelus) at Universiti Malaysia Kelantan, Bachok Campus, Kelantan, Malaysia - Kamarul Hambali; Nadia Zakaria; Norashikin Fauzi; Aainaa Amir (Universiti Malaysia Kelantan, 2015)
The behavioural patterns of six captive ostriches (Struthio camelus) were studied at Universiti Malaysia Kelantan, Bachok Campus between July and September 2014. The main purpose of the study was to determine the behavioural patterns of ostriches in captivity to provide the useful information for better management action. The ostriches were observed daily for 11 hours from 0700 hrs until 1800 hrs for 45 days by using the focal sampling technique. Six categories of behavioural patterns were observed namely resting, locomotion, ingestive, comfort, aggression and thermoregulation. The highest behaviour observed was walking compared to other behaviours, while the lowest was running. The result of the study showed a significant difference of behavioural patterns of captive ostriches between different observational periods except for locomotion and aggression behaviours. The finding of the study showed that ostriches reared in captivity possessed similar behavioural patterns to those remaining in the wild, although some captive circumstances imposed minor differences.